Review article: FODMAPS, prebiotics and gut health‐the FODMAP hypothesis revisited. Issue 2 (20th June 2020) - Gibson, Peter R.; Halmos, Emma P.; Muir, Jane G.
Summary: Background: Restriction of dietary FODMAP intake can alleviate symptoms in patients with irritable bowel syndrome. Because many FODMAPs have prebiotic actions, there is concern that their dietary restriction leads to dysbiosis with health consequences, and their intake is being encouraged by addition to foods and via supplements. Aims: To examine the hazards and benefits of high and low FODMAP intake. Methods: Current literature was reviewed and alternative hypotheses formulated. Results: Low FODMAP intake reduces abundance of faecal Bifidobacteria without known adverse outcomes and has no effect on diversity, but the reduction in bacterial density may potentially be beneficial to gut health. Supplementary prebiotics can markedly elevate the intake of FODMAPs over levels consumed in the background diet. While this increases the abundance of Bifidobacteria, it adversely affects gut health in animal studies by inducing colonic mucosal barrier dysfunction, mucosal inflammation and visceral hypersensitivity. Rapid colonic fermentation is central to the identified mechanisms that include injury from high luminal concentrations of short‐chain fatty acids and low pH, and inflammatory effects of increased endotoxin load and glycation of macromolecules. Whether these observations translate into humans requires further study. Opposing hypotheses are presented whereby excessive intake of FODMAPs might have health benefits via prebiotic effects, but might also be injurious and contribute to the apparent increase in functional intestinal disorders. Conclusions: Reduced FODMAP intake has few deleterious effects on gut microbiota. Consequences (both positive and negative) of excessive carbohydrate fermentation in the human intestines from elevated FODMAP intake require more attention.